2010
DOI: 10.1093/brain/awp333
|View full text |Cite
|
Sign up to set email alerts
|

Reactive microgliosis: extracellular μ-calpain and microglia-mediated dopaminergic neurotoxicity

Abstract: Microglia, the innate immune cells in the brain, can become chronically activated in response to dopaminergic neuron death, fuelling a self-renewing cycle of microglial activation followed by further neuron damage (reactive microgliosis), which is implicated in the progressive nature of Parkinson's disease. Here, we use an in vitro approach to separate neuron injury factors from the cellular actors of reactive microgliosis and discover molecular signals responsible for chronic and toxic microglial activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 52 publications
4
69
0
Order By: Relevance
“…Our results show that, under certain conditions such as ␣-syn overexpression, calpain-1 can be released to the extracellular environment. It has been observed that 1-methyl-4-phenylpyridiniumtreated dopaminergic cells can release soluble factors such as calpain that activate microglia and are selectively toxic to other neurons (Levesque et al, 2010). Calpains are also externalized during certain inflammatory processes and play a role in the microenvironment of inflammatory cells (Ménard and el-Amine, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that, under certain conditions such as ␣-syn overexpression, calpain-1 can be released to the extracellular environment. It has been observed that 1-methyl-4-phenylpyridiniumtreated dopaminergic cells can release soluble factors such as calpain that activate microglia and are selectively toxic to other neurons (Levesque et al, 2010). Calpains are also externalized during certain inflammatory processes and play a role in the microenvironment of inflammatory cells (Ménard and el-Amine, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial impairment, due to genetic factors and/or environmental exposure to toxins could be the primary event triggering the pathological process. In this case, it is possible to hypothesize that microglia may become chronically activated in response to primary mitochondrial impairment and/or dopaminergic neuronal death, fueling a vicious cycle of microglial activation followed by further neuronal damage [84]. Indeed, there is evidence supporting the hypothesis that activated glial cells are able to damage dopaminergic neurons [85,86].…”
Section: Mitochondrial Impairment Neuroinflammation and Neurodegenementioning
confidence: 99%
“…NOX2 is strongly upregulated in different CNS disorders where it generates large amounts of ROS. NOX2 activation is thought to regulate microglia activation, a hallmark of inflammatory gliosis observed in neuroinflammatory degenerative disorders [17,85]. As a major source of ROS, NOX2 can induce direct neuronal damage [128] and maintain microglial cells in an activated stage where they produce neurotoxic molecules like peroxynitrite and other inflammatory molecules [94].…”
mentioning
confidence: 99%